MANAJEMEN MODAL KERJA DAN PROFITABILITAS PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Layyinaturrobaniyah, Layyinaturrobaniyah (Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine and analyze the effect of working capital management measured using the Current Assets to Total Assets Ratio (CATAR) and Current proxy to Total Assets Ratio (CLTAR) proxy to profitability measured by calculating the Return on Assets (ROA) ratio. By using the purposive sampling method obtained as many as 11 samples of Automotive and Component companies listed on the Indonesia Stock Exchange for the period 2012-2016. The analytical method used is multiple linear regression analysis. The results showed that the Current Assets to Total Assets Ratio (CATAR) had a significant positive effect on ROA. Furthermore, the Current Liabilities to Total Assets Ratio (CLTAR) has a significant negative effect on ROA. Meanwhile, based on simultaneous testing, the results show that the CATAR and CLTAR variables together have an effect on ROA. For this reason, the company needs to analyze the management of its working capital well because the proportion of working capital owned can affect the profitability of the company.Â Key Words: Working capital management, Profitability, Current Assets to Total Assets Ratio (CATAR), Current Liabilities to Total Assets Ratio (CLTAR), Return on Assets (ROA)